2007
DOI: 10.1097/01.gme.0000236937.36078.f4
|View full text |Cite
|
Sign up to set email alerts
|

Women's health during mid-life survey

Abstract: CAM use by women to alleviate menopausal symptoms is common, with several therapies perceived to be effective. Although a significant proportion of women may use CAM in conjunction with pharmaceuticals, relevant communication between medical practitioners and patients remains inadequate and may expose the patient to potential drug-herb interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(24 citation statements)
references
References 30 publications
1
22
1
Order By: Relevance
“…The majority of symptoms reported were similar to those found in the non-Indigenous population of Australia [1,3,4,8,52]. Most notable was the reporting of the ‘traditional’ hot flushes and night sweats.…”
Section: Discussionmentioning
confidence: 52%
“…The majority of symptoms reported were similar to those found in the non-Indigenous population of Australia [1,3,4,8,52]. Most notable was the reporting of the ‘traditional’ hot flushes and night sweats.…”
Section: Discussionmentioning
confidence: 52%
“…However, despite the effectiveness of HRT [2], many women refuse or discontinue treatment because of side effects such as vaginal bleeding, bloating and breast tenderness or due to concerns about an increased risk of cancer or other HRT-linked conditions [3-8]. Therefore, many women are seeking safer alternative therapies to relieve symptoms and improve quality of life [9-19]. A large number of these treatments come under the broad term of Complementary and Alternative Medicine (CAM).…”
Section: Introductionmentioning
confidence: 99%
“…Although a number of studies have investigated the use of CAM during the menopausal transition [9-19], only one study was conducted in Italy [20], which investigated the use of HRT and other treatments for menopausal syndrome amongst a convenience sample of female medical doctors and the wives of doctors.…”
Section: Introductionmentioning
confidence: 99%
“…Current evidence does not support the use of most complementary medicines (CM) for VMS, with popular treatments such as black cohosh shown to be ineffective [15,16] and only modest benefits reported with soy [17]. Yet, over half of the women surveyed in a 2006 Sydney study reported using CM for their menopausal symptoms, with acupuncturists being the second most popular therapists visited [18]. …”
Section: Introductionmentioning
confidence: 99%